Crustal Structure Beneath the Wabash Valley Seismic Zone From the Joint Inversion of Receiver Functions and Surface‐Wave Dispersion: Implications for Continental Rifts and Intraplate Seismicity. Issue 7 (22nd July 2019) - Aziz Zanjani, Asiye; Zhu, Lupei; Herrmann, Robert B.; Liu, Yuchen; Gu, Zhiyuan; Conder, James A.
Abstract: Seismicity of several intraplate seismic zones in the North American midcontinent is believed to be related to reactivation of ancient faults in Precambrian continental rifts by the contemporary stress field. Existence of such a rift system beneath the Wabash Valley Seismic Zone (WVSZ) is not clear. Here we obtained a crustal structural image along a 300‐km‐long profile across WVSZ using a dense linear seismic array. We first calculated teleseismic receiver functions of stations and applied the Common‐Conversion‐Point stacking method to image crustal interfaces and the Moho. We then used ambient noise cross correlation to obtain phase and group velocities of Rayleigh and Love waves. Finally, we jointly inverted the receiver function and surface wave dispersion data to determine shear wave velocity structure along the profile. The results show a thick (50‐ to 60‐km) crust with a typical Proterozoic crustal layering: a 1‐ to 2‐km thick Phanerozoic sedimentary layer, an upper crust ∼15 km thick, and a 30‐ to 40‐km‐thick lower crust. The unprecedented high‐resolution image also reveals a 50‐km‐wide high‐velocity body above an uplifted Moho and several velocity anomalies in the upper and middle crust beneath the La Salle Deformation Belt. We interpreted them as features produced by magmatic intrusions in a failed, immature continental rift during the end of Precambrian. Current seismicity in WVSZ is likely due to reactivation of ancient faults of the rift system by a combination of stress fields from the far‐field plate motion and prominent crustal and upper mantle heterogeneities in the region. Key Points: A high‐resolution crustal structure image across the Wabash Valley Seismic Zone has been obtained using a 300‐km‐long dense seismic array The image reveals a high‐velocity body atop an uplifted Moho and several velocity anomalies in the crust beneath the center of Wabash Valley The anomalous crustal structural features suggest mantle magmatic intrusions in an immature continental rift during the end of Precambrian